2018
DOI: 10.1007/s00405-018-4938-z
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing eustachian tube function in patients with symptoms of chronical Eustachian tube dysfunction by pressure chamber measurements

Abstract: Pressure chamber-based measurements enable an objective and safe dynamic testing of the ET pressure equalization function in patients with ETD. In addition, via continuous impedance measurement, it is possible to identify patients with patulous ETD and baro-challenge-induced ETD. These results are a relevant preliminary work to identify and assess patients for different therapy options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Another diagnostic tool for evaluation of ETD is the pressure chamber test, which involves ear‐specific continuous tympanometric impedance measurements during compression and decompression in a hyper/hypobaric chamber. By measuring ETOP, objective, quantitative, and reliable parameters across a dynamic setting have been reported for normal, healthy individuals, and patients with both obstructive ETD and specifically BCETD 51–53 . Passive ETOP has been found to be much higher in patients with BCETD (5 ± 2.9 kPa) compared to healthy individuals (3.0 ± 1.5 kPa) 51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another diagnostic tool for evaluation of ETD is the pressure chamber test, which involves ear‐specific continuous tympanometric impedance measurements during compression and decompression in a hyper/hypobaric chamber. By measuring ETOP, objective, quantitative, and reliable parameters across a dynamic setting have been reported for normal, healthy individuals, and patients with both obstructive ETD and specifically BCETD 51–53 . Passive ETOP has been found to be much higher in patients with BCETD (5 ± 2.9 kPa) compared to healthy individuals (3.0 ± 1.5 kPa) 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…By measuring ETOP, objective, quantitative, and reliable parameters across a dynamic setting have been reported for normal, healthy individuals, and patients with both obstructive ETD and specifically BCETD 51–53 . Passive ETOP has been found to be much higher in patients with BCETD (5 ± 2.9 kPa) compared to healthy individuals (3.0 ± 1.5 kPa) 51,52 . More recently, it has been shown that patients with chronic ETD have improvements in passive ETOP after BDET from 5.1 ± 3.7 to 3.1 ± 1.9 kPa ( p = 0.001) and that the pressure chamber test could be a more reliable assessment tool for postdilation improvement than patient‐reported outcomes 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tests of ET function were performed at a stable ambient pressure and not under conditions of baro-challenge. Pressure chamber studies have been performed to explore ET ME pressure equalisation [Doyle et al, 2014;Meyer et al, 2018;Schwarz et al, 2019], but while valuable research tools, pressure chambers are not feasible instruments for routine clinical use.…”
Section: Limitationsmentioning
confidence: 99%